어머니의 양육 스트레스, 사회적 지원과 부모효능감이 양육행동에 미치는 영향 - 신숙재(Suk Jea Shin); 정문자(Moon Ja Chung) (Korean Journal of child studies, 1998)
The purpose of this study was to investigate causal relationships among parenting stress, social support, parenting efficacy, and mothers' parenting behaviors as a function of child's sex. The subjects were 419 boys and 414 girls in the 3rd grade of elementary schools in Inchon city, and their mothers. Conflict Tactics Scales (Straus, 1979), Parenting Stress Index (Abidin, 1990), and Parenting Sense of Competence (Gibaud-Wallston & Wandersman, 1978) were revised for use in this research. A modified version of the Social Support Scale (Pak, 1985) and Teamwork of Parenting Alliance Inventory (Abidin, 1988) were used. The data were analyzed with one way ANOVAS, Pearson's correlations, and covariance structural analysis by the LISREL 8.03 program. The results of this study were: (1) The more mothers felt parenting stress and the less they perceived social support and parenting efficacy. (2) The process leading to mothers' coercive parenting behaviors differed as a function of child's sex. For mothers of boys, parenting stress and social support had an indirect effect on coercive parenting behaviors through the mediation of parenting efficacy. For mothers of girls, however, parenting stress had a direct effect on coercive parenting behaviors.